A new approach to extraordinary efficient protection against COVID 19 based on nanotechnology - Jokanović Vukoman; Živković Marija; Zdravković Nemanja (Serbian Medical Society - Dental Section, Belgrade, 2020)
A new approach to the protection against infections caused by bacteria and various viruses, including SARS-CoV-2 is described. In concrete example, protective filters and ALBO nanosilver masks showed extraordinary efficiency in protection against Staphylococcus aureus. These results show that it highly overcomes the efficiency of ordinary surgical masks. Besides, systematic meta-analysis given for ordinary surgical masks and filters N95 for masks and respirators, showed no statistical difference between them in the case of SARS-CoV-2. On the base our experimental data and systemic meta-analysis given in this paper, it can be concluded that ALBO nanosilver masks have significant advantages, and show a very perspective concept of developing new protective gear.